1999
DOI: 10.1037/1076-8971.5.2.388
|View full text |Cite
|
Sign up to set email alerts
|

Jurors' perceptions of hearsay in child sexual abuse cases.

Abstract: The authors examined jurors' perceptions of child victims who testified in court and adult witnesses who repeated children's hearsay statements. Data were collected from criminal courts in 2 major U.S. cities (42 juries and 248 jurors). After deliberating in child sexual abuse trials, jurors completed a detailed questionnaire concerning their perceptions of the main child victim involved in the case and the adult who spoke with the child prior to trial about abuse and who testified about what the child disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 19 publications
6
105
0
Order By: Relevance
“…Thus the children studied by Sayfan et al were largely rated as having neutral expressions, while those studied by Wood et al were relaxed or neutral. These findings, like our own, underscore that children being interviewed about abuse do not behave as adults expect and this may have important implications for perceptions of children's credibility (e.g., Golding-Meadow & Singer, 2003;Myers et al, 1999;Regan & Baker, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…Thus the children studied by Sayfan et al were largely rated as having neutral expressions, while those studied by Wood et al were relaxed or neutral. These findings, like our own, underscore that children being interviewed about abuse do not behave as adults expect and this may have important implications for perceptions of children's credibility (e.g., Golding-Meadow & Singer, 2003;Myers et al, 1999;Regan & Baker, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…Research has shown that a child's age is one of the most influential factors in how mock jurors perceive the credibility of child witnesses. In sexual abuse cases, children who are younger than 12 years of age are typically perceived as more credible than adolescent and adult victims (Myers et al, 1999;Nightingale, 1993). When asked why, mock jurors often report that young children lack the cognitive ability and sexual knowledge that is typically needed to make a false allegation (Bottoms & Goodman, 1994;Duggan et al, 1989;Gabora, Spanos, & Joab 1993;Goodman, Bottoms, Hersocvici, & Shaver, 1989;Nightingale, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This question was addressed by John Myers et al (1999)Myers, Redlich, Goodman, Prizmich and Imwinkelried-in a questionnaire study of 248 American jurors (representing 42 juries), all of whom had just served as jurors in child molestation or child exploitation trials. At least one child testified live in court in each of these trials, as did at least one adult who testified about the child's out-of-court disclosure of abuse.…”
Section: Hearsay Evidencementioning
confidence: 99%